2007
DOI: 10.1590/s0100-40422007000400030
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chemical elements in africanized Apis mellifera (Hymenoptera: Apidae) honey samples from the State of Piauí, Brazil

Abstract: Recebido em 28/6/06; aceito em 30/8/06; publicado na web em 27/4/07Honey is a food used since the most remote times, appreciated for its characteristic flavor, considerable nutritional value and medicinal properties; however, little information exists about the presence of chemical elements in it. The objectives of this work were to determine the chemical elements present in 38 honey samples, collected directly from beekeepers from the State of Piauí, Brazil and to verify whether they presented any contaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
3
9
2
Order By: Relevance
“…In this study, the percentage of reducing sugars in the samples ranged from 66.2 g/100 g to 80.1 g/100 g. Our findings were similar to those of Ouchemoukh, Louaileche, and Schweitzer (2007). The values found for total sugar content in this study ranged from 66.7 to 85.4 g/100 g. These levels are close to those obtained by Arruda, Marchini, Moreti, Otsuk, and Sodré (2005), Komatsu, Marchini, and Moreti (2002), Moreti, Sodré, Marchini, and Otsuk (2009), and Sodré et al (2007), who found total sugar contents of 67.8e88.3 g/ 100 g for Brazilian honey samples of different floral origins.…”
Section: Physical and Chemical Resultssupporting
confidence: 90%
“…In this study, the percentage of reducing sugars in the samples ranged from 66.2 g/100 g to 80.1 g/100 g. Our findings were similar to those of Ouchemoukh, Louaileche, and Schweitzer (2007). The values found for total sugar content in this study ranged from 66.7 to 85.4 g/100 g. These levels are close to those obtained by Arruda, Marchini, Moreti, Otsuk, and Sodré (2005), Komatsu, Marchini, and Moreti (2002), Moreti, Sodré, Marchini, and Otsuk (2009), and Sodré et al (2007), who found total sugar contents of 67.8e88.3 g/ 100 g for Brazilian honey samples of different floral origins.…”
Section: Physical and Chemical Resultssupporting
confidence: 90%
“…These values are lower than those recorded in other studies such as 3.1 μg.g −1 Özcan et al (2006) and 1.5 μg.g −1 Nalda et al (2005). Sodré et al (2007) found a maximum value of 0.3 μg.g −1 in Brazilian honeys, which is much closer to our results. This can probably be explained by the acid characteristics of Europeans honeys, with pH values different from Brazilian honeys (Paramás et al 2000;Juszczak et al 2009).…”
Section: Variation In Element Concentrationssupporting
confidence: 91%
“…The high Ca values in samples collected in Teresópolis differ considerably from values recorded in other studies (Marchini et al 2005;Sodré et al 2007, Santos et al 2008. Sodré et al (2007) found a maximum calcium concentration of 76.8 μg.g -1 .…”
Section: Seasonality Of K and Ca Concentration In Honeycontrasting
confidence: 83%
See 2 more Smart Citations